Pengaruh Giro Wadiah, Deposito Mudharabah, dan Tabungan Mudharabah Terhadap Profitabilitas Bank Umum Syariah di Indonesia (Studi Kasus Pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) Tahun 2019-2023) - Ingra Sovita; Mustika Anggun Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of savings products, namely wadiah demand deposits, mudharabah deposits, and mudharabah savings on the profitability of Islamic Commercial Banks, using Return on Assets (ROA) as the main indicator of profitability. This study was conducted in 2019-2023 with a focus on Islamic Commercial Banks operating in Indonesia. This study uses a quantitative research method. The population in this study were 14 Islamic Commercial Banks in Indonesia. The sampling technique used was purposive sampling. The number of samples in this study was 11 Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK). The test tool used was SPSS 21. The results of this study indicate that wadiah giro has a significant value of 0.001 < 0.05 and a t-count value of 4.124 > 1.690 so that the wadiah giro variable has a positive and significant effect on the profitability of Islamic Commercial Banks, for the mudharabah deposit variable shows that the significant value is 0.587 > 0.05 and the t-count value is 0.548 < 1.690 so that the mudharabah deposit variable does not have a significant effect on the profitability of Islamic Commercial Banks, mudharabah savings shows that the significant value is 0.035 < 0.05 and the t-count value is 2.195 > 1.690 so that the mudharabah savings variable has a positive and significant effect on the profitability of Islamic Commercial Banks. Simultaneously, it has a significance value of 0.01 < 0.05 and a calculated F value of 6.604 > 2.83, so it can be concluded that the variables of wadiah demand deposits, mudharabah deposits and mudharabah savings have a positive and significant effect on the profitability of Islamic Commercial Banks.